2004
DOI: 10.1111/j.1745-459x.2004.tb00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sampling Conditions on Temporal Perception of Bitterness in Yerba Mate (Ilex Paraguariensis) Infusions

Abstract: Time‐intensity (TI) methodology and a trained panel were used to characterize the perceived bitterness of Yerba mate (YM) Ilex paraguariensis infusions. Two sampling procedures (sip and spit; sip and swallow) and two conditions for residence time in mouth (free or fixed duration of 5 s until spit or swallow) were evaluated. At a fixed duration the maximum bitterness as well as the time to reach it showed a significant YM concentration dependence. No change on bitterness was observed by swallowing or spitting Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Descriptors of these characteristics that have shown to differentiate products are shown in Table 8 (Santa Cruz 2002; Cruz and others 2003). Consumer panelists have also been used to test the bitterness (Calvino and others 2004). …”
Section: Technological Considerationsmentioning
confidence: 99%
“…Descriptors of these characteristics that have shown to differentiate products are shown in Table 8 (Santa Cruz 2002; Cruz and others 2003). Consumer panelists have also been used to test the bitterness (Calvino and others 2004). …”
Section: Technological Considerationsmentioning
confidence: 99%
“…In all cases, panelists, were instructed to swallow the sample at a fixed time of 5 s, but were asked to suggest modifications if they considered that this interval was not appropriate. Calviño et al (2004) studied different sampling (spit or swallow) and mouth residence procedures (5 s or free duration and spit/swallow) to characterize the bitterness of Yerba mate infusions, concluding that it is important to establish a fixed time protocol. During this preliminary data collection it was observed that the perception of bitterness lasted for up to 90 s, therefore the "time-window" presented by the sensory analysis software was set at 90 s for each attribute.…”
Section: Panel and Panel Trainingmentioning
confidence: 99%
“…They suggested that participants may have experienced difficulties making ratings while doing something unnatural such as expectorating. Calviño, Fraga, and Garrido (2004) observed no differences in the intensity of bitterness when infusions of yerba mate were evaluated by spitting versus swallowing using time-intensity methodology. Kelly and Heymann (1989) found no difference in thresholds for salt in kidney beans or for fat in milk when determined using either a swallowing or a spitting tasting protocol.…”
Section: Swallowing Versus Expectorating Impacts On Taste and Odor mentioning
confidence: 83%
“…They suggested that participants may have experienced difficulties making ratings while doing something unnatural such as expectorating. Calviño, Fraga, and Garrido () observed no differences in the intensity of bitterness when infusions of yerba mate were evaluated by spitting versus swallowing using time‐intensity methodology.…”
Section: Introductionmentioning
confidence: 99%